Social Impact of Gold Mining: Analysis from the Behavioral Economy - Flórez, Jesús (2021)
It is proposed to develop a research exercise at the municipal level to determine the impacts of mining on local communities. A particular type of mining exploitation is prioritized, which is the exploitation of gold. It is proposed to analyze the changes in the behaviors of the communities surrounding this type of mining exploitation, behaviors that in turn are related to economic decisions. The question to be resolved is: What is the impact of establishing a new gold mining project on a community and how do the economic, social and behavioral dynamics change in the territory? To resolve this question, an impact evaluation is proposed based on a comparative analysis in the department of Antioquia between mining municipalities (treatment group) and non-mining municipalities (control group). The evaluation aims to address three main issues: I) the curse of natural resources at the local level, II) community governance, III) social accountability (citizen oversight). These issues will be approached from the theoretical developments of behavioral economics.